A Study of Class Meetings in VR: Student Experiences of Attending Lectures and of Giving a Project Presentation - Yoshimura, Andrew; Borst, Christoph W. (Frontiers in Virtual Reality, 2021)
We study student experiences of social VR for remote instruction, with students attending class from home. The study evaluates student experiences when: 1) viewing remote lectures with VR headsets, 2) viewing with desktop displays, 3) presenting with VR headsets, and 4) reflecting on several weeks of VR-based class attendance. Students rated factors such as presence, social presence, simulator sickness, communication methods, avatar and application features, and tradeoffs with other remote approaches. Headset-based viewing and presenting produced higher presence than desktop viewing, but had less-clear impact on overall experience and on most social presence measures. We observed higher attentional allocation scores for headset-based presenting than for both viewing methods. Headset-based presenting produced higher perceived emotional and behavioral interdependence than desktop lecture viewing. For headset VR, there were strong negative correlations between simulator sickness (primarily reported as general discomfort) and ratings of co-presence, overall experience, and some other factors. This suggests that comfortable users experienced substantial benefits of headset viewing and presenting, but others did not. Future VR systems are expected to provide more stable and comfortable visuals, providing benefits to more users. Desktop VR appears to be a good alternative for uncomfortable students, and students report that they prefer a mix of headset and desktop viewing. We additionally provide insight from students and a teacher about possible improvements for VR class technology, and we investigate student opinions comparing viewing and presenting in VR to other remote class technologies.